RANCANG BANGUN CHATBOT ZENO SEBAGAI MEDIA AJAR TATA SURYA DAN BAHASA INGGRIS - Alam, Indra Nurul; Alifandra, Dhafa; Wijirahayu, Suciana; Yuliani, Mentari (ISTEK WIDURI, 2023)
Technology continues to evolve alongside the progress in education, as higher levels lead to higher-quality technological advancements. Education, especially elementary school, is of paramount importance. They typically educate children aged 6 to 13 years. Research findings show that media such as images, videos, and texts can enhance comprehension abilities by up to 90% for children in this age group. Therefore, digital technology can play a crucial role in assisting elementary school children in achieving this level of understanding. Through chatbot digital tool, educational materials comprising images, videos, and texts hoping to motivate students to review the lesson. We developed the chatbot using the Rapid Application Development (RAD) to the application quickly and iteratively. The results of the chatbot testing received positive responses from teachers and students. Based on the evaluation, 90% of students reported feeling motivated and assisted in their learning while using the chatbot Zeno. Thus, the conclusion is that the chatbot can effectively aid the learning processof English and Solar System.